Dynamic Behaviour of Submerged Floating Tunnels under Seismic Loadings with Different Cable Configurations - Wahyuni, Endah; Budiman, Ery; Raka, I Gusti Putu (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2012)
The paper presents the dynamic behavior of a Submerged Floating Tunnel (SFT) in the Seribu Archipelago crossing under seismic loadings by using the different cable configurations. The SFT is a tubular structure submerged in the water at a fixed depth, which features several advantages from the structural and environmental impact points of view. In particular, the structural system is suited for waterway crossings in seismicity zones. Its interaction with the water provides additional damping and inertia to the system. To evaluate the SFT structural response of seismic loadings, a response spectrum analyses were carried out, in which the ground multi-support excitation is considered. The investigation of the different cable system configurations were also carried out. Both static and dynamic analyses were carried to find the optimal configuration of the structural system. Although the paper has had a definitive conclusion yet, the results gave useful indications of responses of Submerged Floating Tunnels subjected to earthquake. The SFT with two cable diagonals perpendicular with SFT’s body (called Model C) shows the optimal structural configuration compared with others.